PKM Kelompok Pengolah Ikan Tuna Asap Di Desa Singa Kecamatan Herlang Kabupaten Bulukumba - Harlina Harlina; Ernaningsih Ernaningsih; Andi Nirwana; Kasmawati Kasmawati; ST. Hadijah; Andi Hamdillah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The Community Partnership Program (PKM) aims to solve the problems faced by the Laris Manis Tuna business group in Singa Village, Herlang District, Bulukumba Regency, from the aspect of improving quality, production quantity and financial management. The solutions offered from this program are increasing the production of quality and hygienic smoked tuna using closed system smoking technology, training on packaging smoked tuna products using a vacuum sealer, and training in financial management by keeping daily financial records. The implementation method is a participatory method in which group members are directly involved. After the implementation of this activity there was an increase in partner knowledge and skills, as well as an increase in the quality of smoked tuna products. Partners able to make financial reports so that the financial condition is correctly described which can be used for making business decisions. The output after the implementation of the activity is closed-system smoking technology which makes smoked tuna products of higher quality and hygiene, partners have daily financial records, attractive packaging designs, and publication of devotional journals.